Nästa generations syn på skogsägandet och skogsägarrörelsen - Malmqvist, Johan (2011)

(untitled)
The future of the forest owners’ associations are intimately coupled to the development in family forestry. Forecasts have been made that predicts that the number of forest properties for sale on the open market will increase as the interest among the children of the property owners is considered to decrease. The associations are also affected by continuing individualism in the society which may affect attitudes to as well as interest in membership. The objective of this study was to study the attitudes among grown-up children of members in a forest owners association towards overtaking the forest property as well as membership in a forest owners association. The study focused on grown-up children who were between 30 and 50 years old. To reach them, 800 members between 55 and 70 years old were contacted to gather contact information to their children. After random sampling among siblings to 384 members who provided such information (only one child per member was included in the study), 299 usable answers were gathered using a telephone questionnaire. The majority of the children that answered the questionnaire were between 30 and 35 years old. The proportion of children who today were interested to take over their parents’ property (77.3 %) was comparable to the proportion of today’s forest owners that have acquired their property within their family. Women were significantly less interested to take over their parents’ property. The proportion of children interested to take over the property together with their siblings (43.7 %) was higher than the present proportion of properties that were share-owned. Children who helped their parents with the practical management were significantly more interested to take over their parents’ property. The children were well-acquainted with the forest owners association and three out of four children were interested to become a member, or were already a member, if they were to take over their parents’ property. However, half of the children did not have knowledge of the values of the forest owner association which may imply that the recruitment of members willing to lead the association in the future might become more difficult than it is today.